2016
DOI: 10.1007/s11356-016-7137-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase

Abstract: In the last decade, environmental risks associated with wastewater treatment plants (WWTPs) have become a concern in the scientific community due to the absence of specific legislation governing the occupational exposure limits (OEL) for microorganisms present in indoor air. Thus, it is necessary to develop techniques to effectively inactivate microorganisms present in the air of WWTPs facilities. In the present work, ultraviolet light A radiation was used as inactivation tool. The microbial population was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…An activation of titanium(IV) oxide under visible light irradiation is possible through surface modification with noble metal nanoparticles such as silver, gold, platinum, and palladium. 5,21 In the present study, the effect of metal type, content, as well as an LEDs irradiation source on the photocatalytic and fungicidal activity of titanium(IV) oxide modified with mono-and bimetallic nanoparticles was investigated. 18 Commercial application of photocatalysis is associated with the costs of photocatalytic process, thus it is essential to look for new environmentally friendly light sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An activation of titanium(IV) oxide under visible light irradiation is possible through surface modification with noble metal nanoparticles such as silver, gold, platinum, and palladium. 5,21 In the present study, the effect of metal type, content, as well as an LEDs irradiation source on the photocatalytic and fungicidal activity of titanium(IV) oxide modified with mono-and bimetallic nanoparticles was investigated. 18 Commercial application of photocatalysis is associated with the costs of photocatalytic process, thus it is essential to look for new environmentally friendly light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing number of articles in which LEDs are described as a potential irradiation source for photocatalytic degradation, there are still limited reports on the application of TiO 2 photocatalysis for removal of volatile organic compounds. 5,21 In the present study, the effect of metal type, content, as well as an LEDs irradiation source on the photocatalytic and fungicidal activity of titanium(IV) oxide modified with mono-and bimetallic nanoparticles was investigated. To our best knowledge, there are no reports in which Vis light emitting diodes with λ max = 400 nm and λ max = 460 nm were used for photocatalytic deactivation of microorganisms in the gas phase.…”
mentioning
confidence: 99%
“…Radicals produced during photocatalysis can disrupt cell membranes, and oxidize bioaerosols until mineralisation. It has been reported that photocatalysis induces genetic damage and denaturalization of bioaerosol cells (Boyjoo et al, 2017;Rodrigues-Silva et al, 2017). The aforementioned is called inactivation of bioaerosols and is a photocatalytic activity-dependent characteristic.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Therefore, the immobilization of catalysts on inert carriers such as SiO 2 based materials, cellulose acetate filters, polymeric membranes, and polyethylene terephthalate (PET) (Hosseini et al, 2007;Chuaybamroong et al, 2010;Sánchez et al, 2012;Hinojosa-Reyes et al, 2013;Rodrigues-Silva et al, 2017) has been reported to avoid their loss in continuous systems. Furthermore, among the most common impregnation methods reported is the sol-gel immersion, which has been found suitable for photocatalytic inactivation of bioaerosols (Chuaybamroong et al, 2010;Sánchez et al, 2012;Rodrigues-Silva et al, 2017). Sánchez et al studied the photocatalytic inactivation of real bioaerosols with TiO 2 impregnated in Polyethylene Terephthalate (PET) at a flow of 180 L/min from a laboratory occupied by five people, finding an inactivation efficiency for bacteria up to 76% and without significant inactivation of fungi.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Nevertheless, new promising photocatalytic materials and reactor designs have been recently reported in the literature. To study the inactivation of bacteria and fungi, Rodrigues-Silva et al (2016) carried out experiments in a single-pass annular photoreactor packed with cellulose acetate monolithic structures coated with P25. They found that the survival rate of the microorganisms under study decreased with the catalyst load and the UVA exposure time.…”
Section: Introductionmentioning
confidence: 99%